Enhancing engineering student retention at Indonesian private university through improved interpersonal interactions and social integration - Talar, Yulianti; Gozaly, Jimmy; Vania, Grace (Universitas Sultan Ageng Tirtayasa, 2025)
The high dropout rate among engineering students in Indonesia, particularly at private universities, sets the stage for this research. We explored how interpersonal interaction and social integration influence students' commitment to finishing their degrees. To do this, we collected data through a questionnaire distributed to engineering students at a private university, focusing specifically on those who had just completed their first semester. In total, we gathered 101 responses. Our analysis, using binary logistic regression, revealed two key factors that positively impact student commitment: CSIMILAR, representing a sense of similarity or connection among peers, and CORGPROG, indicating involvement in program-level activities such as student associations, comparative studies, or new student orientations. Further analysis using crosstabulations and correspondence analysis helped clarify the relationship patterns between these factors and other variables. Based on these findings, we recommend that engineering faculty and study program management actively develop various activity groups and organize a diverse range of student events, as these efforts should help strengthen students' commitment to completing their studies.